2014
DOI: 10.3892/etm.2014.2099
|View full text |Cite
|
Sign up to set email alerts
|

Excessive levels of nitric oxide in rat model of Parkinson’s disease induced by rotenone

Abstract: Systemic rotenone models of Parkinson’s disease (PD) are highly reproducible and may provide evidence on the pathogenesis of PD. In the present study, male Sprague-Dawley rats (1-year-old) were subcutaneously administered with rotenone (1.5 mg/kg/day) for six days and observed for the following three weeks. Compared with the control rats, a significant decrease was observed in the body weight and a marked increase was observed in the areas under the behavioral scoring curves in the rotenone-treated rats. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 48 publications
6
28
0
Order By: Relevance
“…Similar results have also been reported by some earlier studies (Xiong et al, 2015). This weight loss could be due to the reduced food intake, disturbance in gastric motility and stool frequency (Xiong et al).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have also been reported by some earlier studies (Xiong et al, 2015). This weight loss could be due to the reduced food intake, disturbance in gastric motility and stool frequency (Xiong et al).…”
Section: Discussionsupporting
confidence: 90%
“…In accord with our findings in human neurons, prior studies in rodents have suggested that aberrant expression of a-syn increases the vulnerability of SNpc neurons to the neurotoxic effects of PQ/MB or Rot (55,56). In rodents, treatment with PQ/MB or Rot causes degeneration of SNpc neurons and locomotor deficits consistent with a Parkinsonian phenotype (57)(58)(59)(60). PQ and Rot are believed to inhibit mitochondrial complex I (8,13,61), whereas MB is reported to inhibit mitochondrial complex I and III, increasing oxidative stress (62,63).…”
Section: Discussionsupporting
confidence: 90%
“…It is a neurotransmitter in the basal ganglia of the central nervous system (CNS), and it is known that its synthesis increases in PD [39]. Previous studies have shown that the activity of iNOS and nNOS, which plays a role in the synthesis of NO, also has a role in the developing of neurodegeneration in PD [40].…”
Section: Discussionmentioning
confidence: 99%